The Defense and Veterans Brain Injury Center Care Coordination Program : assessment of program structure, activities, and implementation - Martin, Laurie T. (Laurie Thayer), 1974- (RAND Corporation research report series, 2013)
Improvised explosive devices have been used extensively against U.S. forces during Operation Enduring Freedom and Operation Iraqi Freedom and have been one of the leading causes of death. Injuries among survivors often include traumatic brain injuries (TBIs). Those recovering from TBIs often find they must coordinate services across multiple systems of care to meet all their medical and psychological health needs. This task is difficult even for those without the cognitive challenges associated with TBI and may prove overwhelming or even impossible, particularly during periods of transition from inpatient to outpatient services or from active duty to veteran status, for example. Although case management and care coordination are readily available for those who have experienced a severe TBI, fewer resources are available for those with symptomatic mild and moderate TBI. This report focuses on a program designed to facilitate care coordination for individuals with mild and moderate TBI, the Defense and Veterans Brain Injury Center Care Coordination Program. It summarizes RAND's assessment of the program's structure, activities, and implementation. To address the goals above, the authors conducted semistructured interviews in person with program administrators and via telephone with regional care coordinators. The subsequent analysis identified innovative practices, continuing challenges, and lessons learned. The recommendations provided here suggest strategies for meeting these challenges while maintaining the benefits possible through this novel approach to care.